Ruby on Rails for PHP and Java Developers - Vohra, Deepak (Springer Berlin Heidelberg : Imprint: Springer, 2007)
About the Author Deepak Vohra is an Oracle Certified Associate and a Sun Certified Java Programmer. Deepak has published in Oracle Magazine, OTN, IBM developerWorks, ONJava. WebLogic Developer's Journal, the XML Journal, the Java Developer's Journal, FTPOnline, and devX. Deepak has an M.S. Degree in mechanical engineering from Southern Illinois University. Features and Benefits Ruby on Rails is compared with PHP and Java. Commonly used technologies such as Ajax, Web Services and LDAP are used with Ruby on Rails. Example applications are provided that may be modified to suit a developer's application. Ruby on Rails is configured with commonly used databases: the MySQL database server, the Oracle database and the SQL Server database. A Ruby on Rails application is hosted on a Ruby on Rails web host. Ruby on Rails for PHP and Java Developers The web framework Ruby on Rails for developing database based web applications provides a Model-View-Controller framework. The required web server WEBrick is included with Ruby on Rails. The framework is configured with the MySQL database by default, but may be configured with another database. The book covers developing web applications with Ruby on Rails. Technologies discussed include Ajax, directory services, and web services. A comparison is made with PHP, the most commonly used scripting language for developing web applications.